Characterization of Bacteriophage Peptides of Pathogenic Streptococcus by LC-ESI-MS/MS: Bacteriophage Phylogenomics and Their Relationship to Their Host - Abril, Ana G.; Carrera, Mónica; Böhme, Karola; Barros-Velázquez, Jorge; Cañas, Benito; Rama, Jose L. R.; Villa, Tomás G.; Calo-Mata, Pilar (Frontiers in Microbiology, 2020)
The present work focuses on LC-ESI-MS/MS (liquid chromatography-electrospray ionization-tandem mass spectrometry) analysis of phage-origin tryptic digestion peptides from mastitis-causing Streptococcus spp. isolated from milk. A total of 2546 nonredundant peptides belonging to 1890 proteins were identified and analyzed. Among them, 65 phage-origin peptides were determined as specific Streptococcus spp. peptides. These peptides belong to proteins such as phage repressors, phage endopeptidases, structural phage proteins, and uncharacterized phage proteins. Studies involving bacteriophage phylogeny and the relationship between phages encoding the peptides determined and the bacteria they infect were also performed. The results show how specific peptides are present in closely related phages, and a link exists between bacteriophage phylogeny and the Streptococcus spp. they infect. Moreover, the phage peptide M*ATNLGQAYVQIM*PSAK is unique and specific for S. agalactiae. These results revealed that diagnostic peptides, among others, could be useful for the identification and characterization of mastitis-causing Streptococcus spp., particularly peptides that belong to specific functional proteins, such as phage-origin proteins, because of their specificity to bacterial hosts.